Experimental determination of parameter dependencies in the combustion process of a radiant tube burner system - Varga, Augustin; Kizek, Jan; Rimar, Miroslav; Staško, Šimon; Dzurňák, Róbert (Frontiers in Energy Research, 2025)
IntroductionThe EU’s environmental and energy policy has set goals for member states in increasing efficiency and effectiveness, reducing emissions, and lowering the consumption of fossil fuels as part of measures to decarbonize industry. An important part of the industrial sector consists of industrial furnaces, which include continuous annealing lines for the heat treatment of steel strips. Industrial furnaces operate with high energy consumption and by optimizing their energy processes it is possible to contribute to the decarbonization of the industry.MethodsThe research in this manuscript focused on the analysis and optimization of an annealing furnace installed within a continuous annealing line. The heating process in the annealing furnace is carried out by indirect heating using radiant tube burners in a protective atmosphere. Based on the analysis of the operation of the burners in the different zones of the annealing furnace, it was necessary to determine the dependencies of the parameters of the combustion process. The experiments investigated the temperatures and the composition of the flue gases at different burner outputs, both individually and in groups according to the zones. ResultsBased on the results from the measurements, the factors influencing the combustion process in the annealing furnace were identified and the thermal operation was optimized based on the O2 content in the flue gas, with 5 and 6% O2 volume as the optimization criterion. DiscussionAfter mathematical relationships were derived and regression analysis was performed, dependencies were established to better distribute the fuel among the burners, resulting in fuel savings of up to 9% of the fuel consumption and CO2 emission reductions of up to 700 tCO2 per year. At the same time, the CO concentration in the flue gas was reduced. The proposed method was verified through control measurements in real operation.